Morphological Degradation of Sago Starch (Metroxylon sp.) Bioplastic of Palopo, South Sulawesi - Pria Gautama; Budiawan Sulaeman; Nurhidayanti Nurhidayanti (Green Engineering Society, 2025)
The growing concern over non-organic plastic waste has driven the development of bioplastics from renewable sources, such as sago starch (Metroxylon sp.), as an environmentally friendly alternative. This study aims to analyze the morphological structural changes of sago starch bioplastics exposed to UV radiation using Scanning Electron Microscopy (SEM). The bioplastics were prepared from sago starch, subjected to controlled UV irradiation, and subsequently examined with SEM to observe microstructural modifications. The results demonstrate that UV radiation significantly induces degradation and structural alterations, characterized by increased surface roughness, and changes in the fracture structure and cross-section of the bioplastic. SEM images show the progression of structural damage at various UV exposure times (24, 48, and 72 hours), illustrating the formation of cracks, micro-cavities, and increased porosity. These findings underscore the importance of understanding UV degradation for developing more environmentally resistant sago bioplastics.